Platelets and vascular inflammation of the brain - Mezger, M.; Göbel, K.; Kraft, P.; Meuth, S. G.; Kleinschnitz, C.; Langer, H. F. (Hämostaseologie, 2015)
There is emerging evidence that platelets have an important role in inflammation beyond their involvement in hemostasis. Platelets can contribute to inflammatory reactions via crosstalk both with immune cells and endothelial cells. Inflamed vessels are characterized by the presence of activated endothelial cells. These activated endothelial cells upregulate receptors necessary for leukocyte recruitment, but also for the adhesion of platelets. Subsequently, immune cells can bind to platelets through adhesion receptors presented on the platelet surface, thus supporting leukocyte recruitment to the vessel wall. There are several neurological diseases associated with vascular inflammation including multiple sclerosis (MS) and stroke. Increased markers of platelet activation could be demonstrated in patients suffering from MS compared to healthy individuals. Reports from murine models indicate that platelets may be of importance for disease progression and severity by mediating leukocyte recruitment as one potential underlying mechanism. Blocking platelet function disease severity was considerably ameliorated. Moreover, processes of tissue remodelling may be influenced by platelet derived mediators. Whether a role of platelets for vascular inflammation can be extrapolated to further neurological diseases will have to be investigated in further in depth experimental and clinical trials.Platelets and platelet associated mechanisms may offer novel starting points to understand neurovascular diseases from a different point of view and to develop novel approaches to access the disease.
Keywords: Platelets; inflammation